Conceptualization of a new generation of smart energy systems and the transition toward them using anticipatory systems - Zahra Heidari Darani (SpringerOpen, 2021)
Abstract Emerging energy systems are inherently different from their conventional counter-parts. To address all issues of these systems, comprehensive approaches of transdisciplinary and post-normal sciences are needed. This article tries to re-conceptualize emerging energy systems using Robert Rosen’s theory of anticipatory system and introduces the concept of the anticipatory smart energy system (ASES). Three important features of an ASES are described and socio-technical considerations for realization of these features are discussed. The article also considers realization of such systems under society 5.0 paradigm and spime techno-culture. In ASESs, the identity of users evolves and new identities are created for energy users, based on the production, consumption, storage, and distributed management of energy. An Anticipatory energy system can manage a common pool of prosumaging.